Pendampingan Pembuatan Pupuk Organik (Kompos) Cair dari Limbah Rumah Tangga di Kecamatan Selemadeg Timur Kabupaten Tabanan - I G.W. Darmadi (Poltekkes Kemenkes Denpasar, 2019)
Household waste is garbage originating from daily activities in households that do not include specific feces and garbage Waste management includes activities: sorting; collection; transportation; processing; and final processing of waste. Household waste treatment includes activities: compaction; composting; material recycling; and / or energy recycling. This community service aims to assist in the production of liquid organic fertilizer (compost) from household waste in the District of East Selemadeg, Tabanan Regency. In this community service, the method used in this facilitation was the method of lecturing, demonstration and accompaniment to the production of liquid organic fertilizer (compost) from household waste. The results of community service were 10 composter units handed over to the village head. 8 units were distributed to PKK cadres. (each hamlet is distributed as much as 1 unit of composter except in the hamlet of Gelijih Pondok 2 composter). The composters have been used to make liquid organic fertilizer (compost) and have produced liquid fertilizer 1 large pocari bottle (2 l) and 6 aqua bottled water ( 600 ml). It is expected that the PKK cadre mothers in the village of Megati should be developed more skillfully to the cadre mothers who have not received a composter device and other housewives.Keywords: Liquid organic fertilizer (compost).